PEMETAAN SEBARAN RTH PUBLIK (TAMAN TEMATIK) KOTA BAUBAU BERDASARKAN SISTEM INFORMASI GEOGRAFIS - Hidayat, Ahmad; Saleh, Fitra (Jurnal Geografi, 2024)
The existence of green open space as a Baubau City park is one of the building blocks of the urban landscape of Baubau City, in addition to functioning as a means of channeling people's aspirations, it is also an effort to realize the green city concept. The lack of information regarding the existence of thematic parks results in the ineffective use of parks as public spaces. The purpose of this study is to provide an overview of the distribution of existing public green open space thematic parks and to provide information related to thematic parks in Baubau City. This research was conducted by applying the interview method to obtain an overview of thematic parks and direct observation to collect spatial data on the location of each thematic park in Baubau City. The result of this study is a description of the location of the thematic park based on a geographic information system (GIS) which is presented in the form of a map.